PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK DI KELAS VIII SMPN 13 PADANG - Fahrira, Vonny Julia (Departemen Matematika, 2024)
Being able to articulate mathematical ideas clearly is a crucial competency for every mathematician. On the other hand, eighth graders at SMP Negeri 13 Padang still have a poor level of this skill. Think Talk Write (TTW) is a cooperative learning approach that addresses this issue. This study aims to describe how eighth graders at SMP Negeri 13 Padang developed their mathematics communication skills through the implementation of the TTW model and to assess whether or not this approach is superior to traditional learning methods. Qualitative research and descriptive research both fall under this umbrella. The participants were eighth graders from SMP Negeri 13 Padang in the fiscal year of 2024/25. Samples were chosen by researchers using a random sampling technique. The evaluation tool utilised was a final exam and quizzes. After applying the TTW model to each indication, the findings of the quiz data analysis provide light on how talents were developed and improved. The results show that the null hypothesis (H0) is rejected, and the TTW model has a significant influence on each indicator (P-value = 0.029).Keywords– at least 3 (three) words and a maximum of 5 (five) words